ONE-STAGE MODIFIED BIPEDICLED SCROTAL FLAP IN PENILE SCLEROSING LIPOGRANULOMA SURGICAL RECONSTRUCTION: A CASE SERIES - Telussa, Arley Sadra; Datusanantyo, Robertus Arian; Kale, Letitia Bellavesta; Djunaedi, Angela (Indonesian Journal of Urology, 2026)
Introduction: Sclerosing lipogranuloma is commonly encountered by urologists and plastic surgeons. Despite potential permanent damage, increasing penile size by injecting unusual substances, usually oil-based, becomes a trend in society. The immediate result, practicality, and affordability of the procedure caused penile shaft deformity, pain, and difficulties in sexual activity. Objective: This study aims to report three cases of modified scrotal flap reconstruction techniques to reconstruct heavily deformed penile shafts with satisfying results. Case(s) Presentation: Three males presented with painful enlarged and deformed penile shaft following a penile enlargement procedure by injection of unusual substances done by non-medical practitioners. Following penile sclerosing lipogranuloma diagnosis, lipogranuloma excision and one-stage modified bipedicle scrotal flap were conducted for all patients. Discussion: A reconstructive procedure is needed to eliminate pain and restore sexual functions. Among available surgical reconstruction techniques, the bipedicled scrotal flap was more suitable in most limited healthcare setting for its less technical complexity, fewer complications, better aesthetic outcomes, and better sexual functions. All cases were reconstructed in a one-stage procedure, they were cost-efficient without losing their features. Conclusion: The one-stage modified bipedicled scrotal flap technique is a beneficial technique for penile reconstruction caused by sclerosing lipogranuloma, especially in health centers where patients reside in distant places. Keywords: Sclerosing lipogranuloma, scrotal flap, reconstruction techniques.